Who is a terrorist? Exploring the utility of interdisciplinary fields - Heba Mohamed Zahra (Review of Economics and Political Science (REPS), 2020)
Purpose - This paper aims to discuss the dilemma of terrorism as a political phenomenon that many political scientists care about; however, they find themselves incapable of explaining some of its aspects and they resort to other disciplines. The second part of the dilemma is related to the incapability of well-established disciplines to provide political scientists with much help. This raises the following question: Will political scientists be able to enhance their knowledge of terrorism with the help of scholars from consolidated and well-established disciplines or with the help of scholars from interdisciplinary fields? Design/methodology/approach - This research depends on the main theories of psychology and of social psychology and adopts a comparative approach to assess the effectiveness of both disciplines in providing political scientists with the knowledge they lack. Findings - In spite of being a well-established and consolidated discipline, psychology is not the perfect discipline that can help political scientists know who a terrorist is. Social psychological theories of aggression provide political scientists with greater ability to understand what psychological and sociological factors motivate a person to turn to aggression and terrorism. Moreover, social psychology developed the "terror management theory" which clarifies various aspects of the phenomenon. Originality/value - This research paper calls the attention of scholars of terrorism to the importance of adopting an interdisciplinary approach to understand the various aspects of a complex phenomenon such as terrorism. The interdisciplinary field adopted will differ according to the research question that a researcher needs to answer.
Keywords: 330; Terrorism; Psychology; Aggression; Interdisciplinary; Social psychology; Social identity